Lubuskie (nie)warte zachodu. O wizerunku, marce i atrakcyjności turystycznej województwa = Lubuskie (not) worth your time in the west: a look at the image, brand, and tourist appeal of the voivodeship - Gandecka, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The tourism industry is highly sensitive to both external and internal factors that shape its performance. The COVID-19 pandemic had a profound impact, leading to an unprecedented 74% decline in international arrivals in 2020 compared to 2019, according to data from the United Nations World Tourism Organisation (UNWTO). However, signs of recovery have emerged, as evidenced by the next UNWTO report. Between January and July 2022, international travel showed a 172% increase compared to the same period in 2021, although arrivals remained 57% below pre-pandemic levels for the corresponding period in 2019.
Keywords: wizerunek; marka turystyczna; atrakcyjność; turystyka; województwo lubuskie; image; tourist brand; attractiveness; tourism; Lubusz Voivodeship